DETERMINAN STRUKTUR MODAL: KAJIAN LIKUIDITAS, PELUANG PERTUMBUHAN DAN ASSET BERWUJUD PERUSAHAAN SUB SEKTOR PROPERTY & REAL ESTATE DI INDONESIA - Ranila Suciati (Universitas Pakuan, 2020)
This study aims to determine the effect of Liquidity, Growth Opportunities, and Tangible Assets on the Capital Structure of Property and Real Estate Companies in Indonesia. The population used in this study are property companies listed on the Indonesian stock exchange in the period 2012-2016. The sample used in this study were 32 property companies in Indonesia by using the purpose sampling method to obtain a representative sample that matches the established criteria. In this study, the data analysis method used is the panel data regression method which is a combination of time series and cross sections in property companies in Indonesia. Research results for property companies in Indonesia The R square value of this model is 0.5126 which means that variations of capital structure that can be explained by the independent variables analyzed are LIQ, GROWTH, and TANG by 51.26 percent and the remaining 48.74 percent explained by other factors not included in this study.